Making the most of support services. - Matheson, Cathy (American City & County, 2002)
Local government officials should investigate the software support services offered when choosing software vendors. Support services cost extra, but they can be useful. In particular, onsite training is needed as the software is being installed and for a period afterwards when users find problems. Some vendors also run education events at conferences, which are useful for learning about new software developments.